Neutrophil, lymphocyte and platelet ratio as a predictor of acute kidney injury after major noncardiac surgery - Shraddha Goswami; Himanshu Tripathi; Snehal Mishra; Manisha Khande; M. Amir Ansari; Ankit Jain (International Journal of Advances in Medicine, 2026)
Background: Acute kidney injury (AKI) is a common complication after major surgery associated with increased morbidity and mortality. Inflammation plays a key role in the pathogenesis of postoperative AKI. This study evaluated the neutrophil-lymphocyte-platelet ratio (NLPR) as a predictor of AKI after major noncardiac surgery. Methods: In a retrospective analysis, we studied 300 patients who underwent major noncardiac surgery. The NLPR was calculated from the complete blood count obtained within 12 hours postoperatively. AKI was defined by the KDIGO criteria. Multivariable logistic regression was used to evaluate the association between NLPR and AKI. Results: AKI occurred in 46 patients (15.3%). The mean NLPR was significantly higher in patients who developed AKI compared to those who did not. On multivariable analysis, NLPR remained an independent predictor of AKI. The area under the receiver operating characteristic curve for NLPR to predict AKI was 0.804. Conclusions: The neutrophil-lymphocyte-platelet ratio is an independent predictor of acute kidney injury after major noncardiac surgery. This simple, widely available biomarker can help identify patients at high risk for this complication.